Allowing the Poor to Share the Earth - Pogge, Thomas (Journal of moral philosophy, 2011)
Abstract Two of the greatest challenges facing humanity are environmental degradation and the persistence of poverty. Both can be met by instituting a Global Resources Dividend (GRD) that would slow pollution and natural-resource depletion while collecting funds to avert poverty worldwide. Unlike Hillel Steiner's Global Fund, which is presented as a fully just regime governing the use of planetary resources, the GRD is meant as merely a modest but widely acceptable and therefore realistic step toward justice. Paula Casal has set forth various ways in which this step might be improved upon. Solid counter-arguments can be given to her criticisms and suggestions. But to specify the best (effective and realizable) design of an appropriate global institutional mechanism with some confidence, economists, political scientists, jurists, environmental scientists, and activists would need to be drawn in to help think through the immense empirical and political complexities posed by this urgent task.